Distributed leadership and teachers? affective commitment to change in Malaysian primary schools: The contextual influence of gender and teaching experience - Thien, Lei Mee (Routledge Journals, Taylor & Francis Ltd, 2021)
Leadership is no longer centred on a singular person, but task sharing through collective interactions of multiple leaders. However, previous studies have mainly focused on the effect of an individual leader on teachers? affective commitment to change. This study investigates the contextual influence of gender and teaching experience on the relationships between distributed leadership functions and teachers? affective commitment to change. Data were gathered from a sample of 531 teachers selected randomly from 30 Malaysian primary schools. Data were analysed using partial least squares structural equation modelling. Findings indicated significant positive effects of leadership support, leadership supervision, cohesive team leadership, and participative decision-making on affective commitment to change. Influence of leadership supervision on affective commitment to change was stronger for female teachers compared to male teachers. Leadership supervision and participative decision-making were positively related to affective commitment to change for early-career teachers. Implications and suggestions for future studies are presented.